2013
DOI: 10.1155/2013/284729
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility to Chagas Disease: An Overview about the Infection and about the Association between Disease and the Immune Response Genes

Abstract: Chagas disease, which is caused by the flagellate parasite Trypanosoma cruzi, affects 8–10 million people in Latin America. The disease is endemic and is characterised by acute and chronic phases that develop in the indeterminate, cardiac, and/or gastrointestinal forms. The immune response during human T. cruzi infection is not completely understood, despite its role in driving the development of distinct clinical manifestations of chronic infection. Polymorphisms in genes involved in the innate and specific i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 135 publications
0
39
0
3
Order By: Relevance
“…This may be attributed in part to the genetic aspects and immune competence of local human populations (Ayo et al, 2013; Deng et al, 2013; Frade et al, 2013; Luz et al, 2016; Nogueira et al, 2012) and/or to parasite genetic heterogeneities. The latter hypothesis finds support in animal studies (that do not strictly recapitulate Chagas disease-associated physiopathologies), which revealed inter-strain variations in complex phenotypes such as parasitemia, virulence, tissue tropism/distribution and pathogenicity (Figure 1) (Andrade et al, 1999; Andrade, 1990; Camandaroba, Pinheiro Lima and Andrade, 2002; de Souza et al, 1996; Laurent et al, 1997; Monteiro et al, 2013; Revollo et al, 1998; Roellig et al, 2010).…”
Section: Trypanosoma Cruzi An 'All-wheel Drive' Parasitementioning
confidence: 99%
See 1 more Smart Citation
“…This may be attributed in part to the genetic aspects and immune competence of local human populations (Ayo et al, 2013; Deng et al, 2013; Frade et al, 2013; Luz et al, 2016; Nogueira et al, 2012) and/or to parasite genetic heterogeneities. The latter hypothesis finds support in animal studies (that do not strictly recapitulate Chagas disease-associated physiopathologies), which revealed inter-strain variations in complex phenotypes such as parasitemia, virulence, tissue tropism/distribution and pathogenicity (Figure 1) (Andrade et al, 1999; Andrade, 1990; Camandaroba, Pinheiro Lima and Andrade, 2002; de Souza et al, 1996; Laurent et al, 1997; Monteiro et al, 2013; Revollo et al, 1998; Roellig et al, 2010).…”
Section: Trypanosoma Cruzi An 'All-wheel Drive' Parasitementioning
confidence: 99%
“…The current consensus states that a failure to down-regulate the inflammatory response, which is maintained by parasite persistence in tissues, appears to play a predominant role. Other contributory factors include sex, age and genotypic features of the patient, route of infection, sustained vector exposure, auto-immune responses and the existence of co-infections (Ayo et al, 2013; Bonney and Engman, 2015; Deng et al, 2013; Frade et al, 2013; Luz et al, 2016; Machado et al, 2012; Nogueira et al, 2012; Tarleton, 2015; Teixeira et al, 2011). As mentioned, a possible role of parasite genotype on Chagas disease progression/outcome has been proposed, though further research supported by novel and robust epidemiologic and diagnostic tools, and appropriate animal models are needed to address this issue.…”
Section: Diagnostic Applications For Chagas D Isease: Present Knowledgementioning
confidence: 99%
“…Of note, T. cruzi infection is a neglected tropical disease with critical social and economic impacts. Triatomine bugs are the main vectors of T. cruzi (Ayo et al, 2013; Pérez‐Molina & Molina, 2018). In brief, an individual becomes infected when metacyclic trypomastigotes of T. cruzi , found in faeces of an infected triatomine bug, penetrate the skin through lesions produced by the bug's oral apparatus following a blood meal on human skin.…”
Section: Ccr5 and Ccr5δ32 In Parasitic Infectionsmentioning
confidence: 99%
“…The parasite can also penetrate the host through mucosal membranes (Pérez‐Molina & Molina, 2018). Humans can also be infected by T. cruzi in other ways, including the ingestion of contaminated food and by congenital or sexual transmission (Ayo et al, 2013).…”
Section: Ccr5 and Ccr5δ32 In Parasitic Infectionsmentioning
confidence: 99%
“…However, one study performed in familial clusters in Brazil displayed evidence that genetic factors may influence both, seropositivity and cardiac outcome traits, and additional data showed that heritability were 0.56 . In line with this, several genetic variants of immune genes have been analyzed in endemic populations finding some associations to risk to infection and/or differential predisposition to the severity of Chagas disease . To date, only one genome wide association study (GWAS) has been performed on Chagasic patients; nevertheless, due to technical limitations there was not conclusive results indicating any association to severity of disease .…”
Section: Genotype and Allele Distribution Of Foxo3 Rs12212067 Polymormentioning
confidence: 99%